PERAN MAHASISWA KAMPUS MENGAJAR ANGKATAN 2 DI SD NEGERI 101954 PANTAI CERMIN - Sihombing, Imelda; Simorangkir, Frida Marta Argareta (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
The teaching campus is a program of the Ministry of Education, Culture, Research and Technology which is part of the independent campus program which aims to provide opportunities for students to learn and develop themselves through activities outside the lecture class. The schools that are the target of the teaching campus are schools with C accreditation and for schools that are remote and in dire need. Plus the Covid-19 pandemic situation that hit Indonesia at that time so that the role of students was very helpful for lost learning due to less than optimal learning at that time. The main objectives of teaching campuses include 1) increasing literacy and numeracy, 2) technology adaptation and 3) managerial school administration. The service method includes the stages of preparation, implementation and evaluation. The preparatory stage includes the process of selecting and accepting teaching campus students, debriefing, fielding, observing and preparing program plans. The implementation phase includes learning activities in an effort to increase literacy and numeracy, technology adaptation and school administration management. The evaluation phase includes the preparation of reports, repairs and collection of reports. The results of the activity include guiding students who will carry out a minimum competency assessment, teaching in class using laptops and other learning media, maximizing the use of the library for study and reading spaces, creating reading corners in class, and assisting school principals in tidying up student data on beneficiaries.